DEVELOPMENT OF FLIPBOOK-BASED DESCRIPTIVE TEXT WRITING TEACHING MATERIALS USING THE HEYZINE APPLICATION FOR CLASS VII JUNIOR HIGH SCHOOL STUDENTS - Nada Salamah; Reni Nur Eriyani; Hestiyani Parai (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This study aims to produce a development product in the form of flipbook-based teaching materials, in the Indonesian language subject in descriptive text material, for grade VII students using the Heyzine application. This study focuses on the development of teaching materials for descriptive text writing skills for grade VII junior high school based on flipbooks assisted by the Heyzine application. The research method used in this study is the Research and Development (R&D) method with the ADDIE (Analysis-Design-Development-Implementation-Evaluation) model. The subjects in this study were 42 grade VII students at SMP Negeri 9 South Tangerang City. Data in this study were collected through observation, interviews, and questionnaires. The results of the research on the development of teaching materials for writing descriptive texts based on flipbooks assisted by the Heyzine application obtained an assessment from media experts with an average percentage of 92.2% of all aspects assessed, with a very feasible category. Material experts gave an assessment with an average percentage of 90% of all aspects assessed, with a very feasible category. The Indonesian language teacher gave an assessment with an average percentage of 99.4% of all aspects assessed, with a very feasible category. Students gave an assessment or response to the teaching materials with an average percentage of 96.1% of all statements submitted. Thus, it can be concluded that the teaching materials for writing descriptive texts based on flipbooks assisted by the heyzine application are very feasible to use in the learning process of writing descriptive texts in class VII.